Epidemiologia molecular e estudo dos fatores de virulência de Staphylococcus aureus resistentes à oxacilina isolados de feridas em pacientes atendidos em unidades básicas de saúde da cidade de Botucatu - Franchi, Eliane Patricia Lino Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Diante da importância de S. aureus resistente à meticilina (Methicillin-resistant Staphylococcus aureus - MRSA) em feridas, este estudo objetivou estudar a prevalência, fatores de risco e epidemiologia molecular de S. aureus coletados de feridas e narinas de pacientes atendidos nas 17 Unidades Básicas de Saúde do município de Botucatu-SP, Brasil. Após a identificação dos isolados de S. aureus, foram realizados: teste de susceptibilidade à 13 drogas antimicrobianas, identificação do gene de resistência (mecA) e dos genes codificadores da Leucocidina PantonValentine- PVL (pvl), enterotoxinas A-E (sea, seb, sec, sed, e see), hemolisinas α, β e δ (hla, hlb e hld), esfoliatinas A, B e D (eta, etb e etd), biofilme (icaAD) e Toxina-1 da Sindrome do choque tóxico – TSST-1 (tst); tipagem molecular por Pulsed-Field Gel Eletroforese (PFGE), Multilocus sequence typing (MLST) e spa typing. Foram incluídos 171 pacientes, dos quais foram isolados 119 S. aureus. Amostras nasais foram coletadas apenas em 74 pacientes do total estudado. A prevalência de S. aureus e MRSA foi de 51,5% e 8,7%, respectivamente. No geral foram isolados 101 MSSA de 73 pacientes, destes 98 foram isolados de feridas e 21 de narinas; e 18 MRSA de 15 pacientes, sendo 4 isolados de narinas e 14 de feridas, com 6 MRSA com SCCmec tipo II e 12 com SCCmec tipo IV. Os isolados mostraram alto nível de resistencia a penicilina (85%), seguido pela eritromicina (27%), gentamicina (12%), clindamicina (11%), e levofloxacina (6%). Não houve resistência ao sulfametoxazol/trimetoprim, ácido fusídico, tigeciclina, quinupristina/dalfopristina e linezolida. A pesquisa por genes de virulência nos 119 isolados de S. aureus sensíveis e resistentes demonstrou que 42% possuem genes para enterotoxina A, 11% para enterotoxina B, 26% para enterotoxina C e 0,8% para enterotoxina D, 100% para o gene icaA, 95,8% para o gene icaD, 97,5% para o gene da hemolisina alfa, 65% para hemolisina beta, 95% para hemolisina delta, 4,2% para TSST-1 e 2,5% para o gene da PVL. Houve associação entre a presença de S. aureus nas narinas a nas feridas (p<0,01), o mesmo ocorreu para MRSA (p<0,01). A análise multivariada para S. aureus, demonstrou associação negativa com idade (OR: 0,94, IC95%: 0,90-0,98, p<0,01), uso de amoxicilina (OR: 0,16, IC95%: 0,04-0,60, p<0,01) e de ciprofloxacina (OR: 0,28, IC95%: 0,08-0,98, p=0,04). Por outro lado, observou-se associação positiva com uso de benzilpenicilina (OR:3,81, IC95%:1,23-11,82, p=0,02). Houve a formação de oito clusters, com predominância de MSSA que apresentaram as STs: 5, 30, 188, 1635 e spa t002. Os 18 MRSA foram caracterizados pelos STs: 5, 8 e 1176 e pelos spas t002, t008 e t062. Foram isoladas linhagens semelhantes aos clones internacionais USA300, USA500 e USA800. Nossos resultados demonstram a presença de clones importantes de MRSA resistentes e virulentos em pacientes atendidos nas diferentes UBSs estudadas.

Given the importance of methicillin resistant S. aureus (Methicillin-resistant Staphylococcus aureus - MRSA) and wounds, this study aimed to study the prevalence, risk factors and molecular epidemiology related to the presence of S. aureus sensitive and resistant to methicillin in wounds of patients who attended BHUs in a city in Sao Paulo state, Brazil. After the identification of S. aureus isolates was performed: susceptibility testing to 13 antimicrobial drugs, identification of the resistance gene (mecA) and the genes encoding Panton-Valentine Leukocidin - PVL (pvl), enterotoxins AE (sea , seb, sec, sed and see) hemolysins α, β and δ (hla, hlb and hld), esfoliatinas A, B and D (eta, etb and etd), biofilm (icaAD) and Toxin-1 syndrome of toxic shock - TSST-1 (tst); Molecular typing by Pulsed-Field gel electrophoresis (PFGE), multilocus sequence typing (MLST) and spa typing. 171 patients were included and 119 S. aureus isolates. Nasal samples were collected only in 74 patients of the total sample. The prevalence of S. aureus and MRSA was 51.5% and 8.7%, respectively. Overall 101 MSSA were isolated from 73 patients, 98 of these were isolated from wounds and 21 nostrils; MRSA and 18 of 15 patients, 4 isolates from nostrils and 14 wounds, with six MRSA with SCCmec type II and 12 SCCmec type IV. The strains showed high-level resistance to penicillin (85%) followed by erythromycin (27%), gentamicin (12%), clindamycin (11%) and levofloxacin (6%). There was no resistance to sulfamethoxazole / trimethoprim, fusidic acid, tigecycline, quinupristin / dalfopristin and linezolid. The search for virulence genes in the 119 isolates of S. aureus sensitive and resistant, 42% demonstrated presence of genes sea, 11% to seb, 26% to sec , 0.8% to sed, 100% to icaA, 95.8% icaD, 97.5% to hla, 65% to hlb, 95% to hld, 4.2% to tst and 2.5% to pvl. There was an association between the presence of S. aureus in the nostrils to the wounds (p<0.01), the same was true for MRSA (p<0.01). Multivariate analysis for S. aureus, showed a negative association with age (OR: 0.94, 95% CI: 0.90-0.98, p<0.01), use of amoxicillin (OR: 0.16, 95% CI: 0.04-0.60, p<0.01) and ciprofloxacin (OR: 0.28, 95% CI: 0.08-0.98, p=0.04). On the other hand, there was a positive association with use of penicillin G (OR: 3.81, 95% CI: 1.23-11.82, p=0.02). There was the formation of eight clusters, with a predominance of MSSA presenting the STs: 5, 30, 188, 1635 and spa t002. The 18 MRSA were characterized by STs 5, 8 and spas 1176 and the t002, t008 and t062. Strains were isolated similar to international clones USA300, USA500 and USA800. Our results demonstrate the presence of important clones resistant and virulent MRSA patients studied in different UBS.
Molecular epidemiology and study of virulence factors of Staphylococcus aureus resistant to oxacillin isolated from wounds in patients treated in basic health units in the city of Botucatu
Keywords: Staphylococcus aureus; MRSA; Epidemiologia; Prevalência; Tipagem; Atenção primária; Prevalence; Epidemiology; Typing; Primary attention